Agricultural Planning in Bihar - Bole, N C (Journal of Soil and Water Conservation, 2022)
In this paper an attempt has been made to assess the agricultural resources of Bihar State in relation to the human and animal population. The intention is to plan a better land-use pattern that will result in a higher agricultural production which can meet the food necessary for the human and animal population of Bihar.The human population in Bihar has in- creased from 29•18 millions in 1921 to 40•23 millions in 1951 that is an increase of 37•87 per cent over 1921. Whereas the average net area shown has increased from 21 •18 million acres in 1921 to 22•19 million acres in 1951, an increase of only +75 per cent over three decades. The cultivated area per capita has been reduced from 73 cents in 1921 to 55 cents a decrease of 24.65 per cent. The population depending on agriculture has in- creased from 7840 per cent in 1931 to 86•05 per cent in 1951.Data required for an accurate estimate are not available in adequate quantity or quality. Several assumptions had to be made and no accuracy is claimed for them. For the pur- pose of this paper, for instance, it has been assumed that no exports or imports of food- stuff take place. If Bihar has to be self- sufficient, it ought to be so. Now there is an import of between 2 and 10 lakh tons of foodgrains per annum.